2017
DOI: 10.1111/1467-923x.12367
|View full text |Cite
|
Sign up to set email alerts
|

Public Services after Austerity: Zombies, Suez or Collaboration?

Abstract: Public services—in the UK and elsewhere—are under considerable pressure, not just from austerity, but also from a variety of social, demographic and technological changes (in effect ‘austerity plus’). In this context, three broad options are open to policy‐makers: continue with tried‐and‐tested approaches while spending less money, which in the UK means a reliance on ‘New Public Management’ (NPM); withdraw completely from certain public services; or develop new approaches to public administration. We argue tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The growth of neo-liberal policies enacted through New Public Management practices of the market, competition, private sector managerialism and ultimately pseudo-profit have been prevalent in reform of public services and rolling back the state since the 1980's (Pollitt, 2018). These developments have again been at the forefront of public sector reforms in the wake of the austerity that has followed the global financial crisis (Griffiths and Kippin, 2017). Perhaps nowhere more so than in English local government, which has experienced a real-term budget cut of nearly 50% since 2011/12 and where there is substantial appetite for alternative ways of "doing more with less" (National Audit Office, 2018).…”
Section: Alternative Service Delivery and Corporatisationmentioning
confidence: 99%
“…The growth of neo-liberal policies enacted through New Public Management practices of the market, competition, private sector managerialism and ultimately pseudo-profit have been prevalent in reform of public services and rolling back the state since the 1980's (Pollitt, 2018). These developments have again been at the forefront of public sector reforms in the wake of the austerity that has followed the global financial crisis (Griffiths and Kippin, 2017). Perhaps nowhere more so than in English local government, which has experienced a real-term budget cut of nearly 50% since 2011/12 and where there is substantial appetite for alternative ways of "doing more with less" (National Audit Office, 2018).…”
Section: Alternative Service Delivery and Corporatisationmentioning
confidence: 99%
“…Previous empirical studies yielded contradictory findings on the link between economic variables and corporatization. Examining trends in corporatization at the local level in England, Ferry et al (2018, p. 479) point out that corporatization greatly increased in the wake of austerity (see also Griffiths & Kippin, 2017). Andrews et al (2020) also found that English local governments experiencing at least some types of fiscal difficulties, such as higher debt service charges, were indeed more likely to set up public corporations.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It has been argued that 'state retreat' offers a rational theoretical explanation of the consequences of national state austerity programmes on socio-ecological partnerships operating under governance modalities [47]. State retreat has been described as a multi-dimensional diminution of the state from (what is often considered) normative positionality, forms, and substance in collaborative governance, towards more basic forms and substance of engagement [48]. This can include state withdrawal from governance fora and decision-making processes [27,42], moving away from the 'collaboration ethic' implicit in normative governance theory [49] and, ultimately, 'rescaling' the role of the state in governance [25,43,50].…”
Section: Conceptualising the Impact Of Austeritymentioning
confidence: 99%